Investment policy review : El Salvador (UN New YorkUS, 2010)
Assesses the regulatory regime against several related criteria (i) whether regulations adequately promote and protect the public interest; (ii) whether regulations adequately promote investment and sustainable socio-economic development; and (iii) whether the methods employed are effective and well administered, given their public interest and development objectives and the legitimate concerns of investors that rules and procedures should not unduly burden their competitiveness.
Keywords: INVESTMENT POLICY